Fuel cell separator material, method for producing fuel cell separator using same, and fuel cell separator

By using a composite material containing conductive particles and binder in the fuel cell separator material and coating a soluble adhesive layer on both sides, the problem of adhesive flow and release film residue is solved, and the improvement of conductivity and drainage performance is achieved.

JP7658940B2Active Publication Date: 2025-04-08TOYOTA JIDOSHA KK +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022134030
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-08-25
Publication Date
2025-04-08
Estimated Expiration
2042-08-25

AI Technical Summary

Technical Problem

During the pressure forming process of existing fuel cell separator materials, adhesive flows to the surface, causing the surface to be covered with adhesive, affecting conductivity; while in the process of using a release film, the residual release film may reduce conductivity. At the same time, traditional impact treatments will reduce the raised portion, resulting in low drainage performance of the flow path.

Method used

A composite material containing conductive particles and binder is used, and a soluble adhesive layer is coated on both sides, forming a convex and concave structure flow path by thermoforming, and then removing the soluble adhesive layer in the polar solvent to expose the conductive particles.

Benefits of technology

The conductivity and drainage performance of the fuel cell separator are improved, the process flow is simplified, and the defects of traditional impact treatment are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658940000005
    Figure 0007658940000005
  • Figure 0007658940000006
    Figure 0007658940000006
  • Figure 0007658940000007
    Figure 0007658940000007
Patent Text Reader

Abstract

To provide a separator material for fuel cells capable of being used for manufacturing a separator for fuel cells which can secure conductivity and improve drainability by a simple step.SOLUTION: A separator material for fuel cells comprises: a composite material that contains a conductive particle and a binder resin; and a soluble resin layer arranged on both surfaces of the composite material.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to a fuel cell separator material, a method for producing a fuel cell separator using the same, and a fuel cell separator. [Background technology]

[0002] A fuel cell is a power generation device that extracts electrical energy through an electrochemical reaction between a fuel gas and an oxidant gas, and is formed by stacking multiple unit cells. A unit cell is formed of an MEA (membrane electrode assembly) or MEGA (membrane electrode gas diffusion layer assembly) in which catalyst layers are arranged on both sides of an electrolyte membrane, and separators that sandwich the MEA and MEGA.

[0003] The separator is made of a material having high gas barrier properties, high electrical conductivity, and appropriate mechanical strength. An example of the material is a composite material made by mixing graphite with a binder resin. The separator is made of such a composite material and is molded by heating so as to have an uneven shape that serves as a flow path for the fuel gas, the oxidant gas, or the coolant.

[0004] The following Patent Documents 1 and 2 disclose techniques that use a composite material in which graphite and a binder resin are mixed as the separator material.

[0005] Patent Document 1 discloses a fuel cell separator having a hydrophilic resin thermosetting coating on the main surface of a substrate made of a graphite resin composite molded body having ribs and grooves on the surface, and that at least a portion of the ribs and grooves is roughened to a surface roughness of 0.15 to 1.5 μm. The document also discloses that the roughening treatment is a blast treatment.

[0006] Patent Document 2 discloses a fuel cell separator molded member that is made by sandwiching a molding material containing graphite and resin between a releasable film, and also discloses a method for manufacturing a fuel cell separator in which the fuel cell separator molded member is thermally compressed and then the releasable film is removed. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2015-38840 A [Patent Document 2] JP 2006-128027 A Summary of the Invention [Problem to be solved by the invention]

[0008] When a composite material in which graphite and binder resin are mixed is used for the separator, the binder resin flows during pressure molding and moves to the surface side (the interface side between the mold and the composite material), and the separator surface becomes covered with resin. Therefore, to improve the conductivity, a blasting treatment is performed as described in Patent Document 1. In the blasting treatment, a blasting agent is sprayed onto the separator surface to remove the resin on the separator surface and adjust the surface roughness of the separator surface. This exposes the conductive particles on the surface, ensuring the conductivity of the separator.

[0009] However, when the blasting process is performed, the convex parts of the separator are mainly scraped off, and the vertical walls connecting the convex parts and the concave parts are hardly scraped off, and the vertical walls are covered with resin. This results in poor drainage of the flow paths. Poor drainage of the flow paths can cause problems such as flooding.

[0010] As disclosed in Patent Document 2, when a separator material having release films arranged on both sides of a composite material is used, the release films are removed after heat molding to produce a separator. In this case, graphite migrates to the surface of the composite material (the interface between the composite material and the release film) during heat molding, making surface treatment such as blasting unnecessary. However, when the release film is removed, there is a risk that the release film will remain on the separator. If the release film remains, there is a concern that electrical conductivity will decrease.

[0011] Therefore, in view of the above-mentioned circumstances, a main object of the present disclosure is to provide a fuel cell separator material that can be used to manufacture a fuel cell separator that can improve drainage performance while ensuring electrical conductivity through a simple process, a method for manufacturing a fuel cell separator using the same, and a fuel cell separator. [Means for solving the problem]

[0012] As one aspect for solving the above problem, the present disclosure provides a fuel cell separator material comprising a composite material containing conductive particles and a binder resin, and soluble resin layers disposed on both sides of the composite material.

[0013] In the separator material, the soluble resin layer may contain a soluble resin that is soluble in a polar solvent. The soluble resin may be polyvinyl alcohol, cellulose, or the like. vinegar The soluble resin layer may contain at least one selected from the group consisting of polystyrene, polyacrylic acid, and starch. The thickness of the soluble resin layer may be 0.5 μm or more and 10 μm or less.

[0014] As one aspect for solving the above problem, the present disclosure provides a method for manufacturing a separator for a fuel cell, comprising: a production step of producing the above-mentioned separator material for a fuel cell; a heat-molding step of imparting an uneven shape that will become a flow path to the surface of the separator material; and, after the heat-molding step, a removal step of immersing the separator material in a polar solvent to remove a soluble resin layer.

[0015] The present disclosure provides a fuel cell separator having an uneven surface that serves as a flow path, the fuel cell separator being formed from a composite material including conductive particles and a binder resin, the uneven surface having convex portions, concave portions, and vertical walls connecting the convex portions and concave portions, and the water contact angle of the surface of the vertical walls being 80° or less. Effect of the Invention

[0016] According to the fuel cell separator material of the present disclosure, a fuel cell separator with improved drainage properties can be manufactured through a simple process while ensuring electrical conductivity. According to the fuel cell separator manufacturing method of the present disclosure, a fuel cell separator with improved drainage properties can be manufactured through a simple process while ensuring electrical conductivity. According to the fuel cell separator of the present disclosure, it is possible to improve drainage properties while ensuring electrical conductivity. [Brief description of the drawings]

[0017] [Figure 1] 2A-2C are cross-sectional schematic diagrams of a method for making separator material 50. [Diagram 2] 1 is a flowchart of a manufacturing method according to an embodiment. [Diagram 3] 1 is a schematic diagram of a manufacturing method according to an embodiment. [Figure 4] FIG. 1 is a schematic diagram of a conventional method for manufacturing a separator. [Diagram 5] 1 is a schematic cross-sectional view of a separator 100. FIG. [Figure 6] 2 is an enlarged schematic view of a cross section of separator 100. FIG. [Figure 7] FIG. 1 is a schematic diagram showing a method for evaluating electrical conductivity. [Figure 8] This shows the results of drainage evaluation (water contact angle evaluation). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The fuel cell separator material of the present disclosure, the method for producing a fuel cell separator using the same, and the fuel cell separator will be described below using one embodiment.

[0019] [Fuel cell separator materials] The fuel cell separator material of the present disclosure will be described using one embodiment of a fuel cell separator material 50. A schematic cross-sectional view of the fuel cell separator material 50 is shown in FIG.

[0020] As shown in FIG. 1, the separator material 50 includes a composite material 30 containing conductive particles 10 and a binder resin 20 , and soluble resin layers 40 disposed on both sides of the composite material 30 .

[0021] The separator material 50 has a sheet shape, and can be given an uneven shape using a predetermined mold. After molding, the soluble resin layer 40 is removed, thereby manufacturing a fuel cell separator. That is, in the separator material 50, 30 is a portion that functions as a separator, and the soluble resin layer 40 is a portion that functions as a protective layer during molding.

[0022] <Conductive particle 10> The conductive particles 10 are materials for ensuring the conductivity of the composite material 30. The type of the conductive particles 10 is not particularly limited, but examples thereof include graphite particles, metal powder, and carbon fibers. Examples of the graphite particles include artificial graphite particles and natural graphite particles. , swelling Examples of the metal powder include powder of a metal compound having corrosion resistance, such as titanium nitride. The conductive particles 10 may be a mixture of a plurality of materials depending on the desired performance. In some embodiments, the conductive particles 10 may be a mixture of graphite particles and carbon fibers. The ratio of the graphite particles and carbon fibers is not particularly limited, but may be, for example, graphite particles:carbon fibers=10:1 to 15:1.

[0023] The primary particle diameter of the conductive particles 10 is not particularly limited, and may be, for example, 1 μm or more, 100 μm or less, or 30 μm or less. The primary particle diameter of the conductive particles 10 is the Feret diameter. The primary particle diameter of the conductive particles 10 can be measured, for example, by using an SEM to measure the primary particle diameters of 10 or more conductive particles 10 and calculating the average value. The number of conductive particles 10 to be measured may be 100 or more.

[0024] In the composite material 30, the content of the conductive particles 10 is not particularly limited, but may be 60% by weight or more, 75% by weight or more, 90% by weight or less, or 85% by weight or less. If the content of the conductive particles 10 is less than 60% by weight, the conductivity of the separator 100 may decrease, and the electrical resistance may increase. If the content of the conductive particles 10 exceeds 90% by weight, the strength of the composite material 30 may decrease.

[0025] <Binder resin 20> The binder resin 20 is a material for ensuring the strength of the composite material 30. The type of the binder resin 20 is not particularly limited, but examples thereof include epoxy resin, phenol resin, and polypropylene resin.

[0026] In the composite material 30, the content of the binder resin 20 is not particularly limited, but may be 10% by weight or more, 15% by weight or more, 40% by weight or less, 30% by weight or less, or 25% by weight or less. If the content of the binder resin 20 is less than 10% by weight, the strength of the composite material 30 may be reduced. If the content of the binder resin 20 exceeds 40% by weight, the conductivity of the composite material 30 may be reduced, and the electrical resistance may be increased.

[0027] <Composite material 30> The composite material 30 may contain materials other than the conductive particles 10 and the binder resin 20, or may be composed of the conductive particles 10 and the binder resin 20. The thickness of the composite material 30 is not particularly limited and may be appropriately set depending on the purpose. For example, it may be in the range of 100 μm to 1000 μm.

[0028] The method for producing the composite material 30 is not particularly limited, and it can be produced by a known method. For example, it can be obtained by mixing the conductive particles 10 and the binder resin 20 in a solvent, and applying and drying the resulting mixture on a release sheet. The method for applying the mixture is not particularly limited, and a known method may be appropriately adopted. For example, the mixture may be applied using a bar coater.

[0029] <Soluble resin layer 40> The soluble resin layer 40 contains a soluble resin that is soluble in a polar solvent. The soluble resin may be contained in an amount of 50% by weight or more in the soluble resin layer 40. From the viewpoint of further improving solubility, the soluble resin may be contained in an amount of 80% by weight or more, 90% by weight or more, 95% by weight or more, or 100% by weight (the soluble resin layer 40 is made of a soluble resin).

[0030] The soluble resin is not particularly limited as long as it is soluble in a polar solvent. From the viewpoint of easy removal by a polar solvent, the soluble resin may contain at least one selected from polyvinyl alcohol, celluloses, polyacrylic acid, and starch. Celluloses are soluble celluloses. vinegar For example, carboxymethyl cellulose vinegar From the viewpoint of improving solubility, the soluble resin may be made of polyvinyl alcohol, may be made of cellulose, may be made of polyacrylic acid, or may be made of starch. The soluble resin may be made of at least one selected from polyvinyl alcohol, cellulose, polyacrylic acid, and starch.

[0031] Types of polar solvents are soluble resins layer There is no particular limitation as long as it can remove 40. Examples include water, lower alcohols of C1 to C3 (e.g., ethanol), glycols, DMSO, phenol, and the like. In consideration of the ease of solvent removal, highly volatile water or ethanol may be used. Water may be selected from the viewpoints of ease of handling and safety.

[0032] The thickness of the soluble resin layer 40 is not particularly limited, but may be 0.5 μm or more and 10 μm or less from the viewpoint of performing good transfer of the uneven shape by the mold and suppressing the unevenness of the thickness of the uneven shape. 40 The thickness may be 5 mm or less, and may be 3 mm or less.

[0033] The method for disposing the soluble resin layer 40 on the sheet-like composite material 30 is not particularly limited, and any known method can be appropriately adopted, such as by using a bar coater or spray coating.

[0034] <Effects> The separator material 50 has a soluble resin layer 40 disposed over both sides of a sheet-like composite material 30. This allows the soluble resin layer 40 to be easily removed by immersing the separator material 50 in a polar solvent after molding, making it possible to manufacture a fuel cell separator in a simple process. Furthermore, the fuel cell separator obtained by this method has good electrical conductivity and high drainage properties, as will be described in more detail below.

[0035] The fuel cell separator material according to the present disclosure has been described above using one embodiment. The fuel cell separator material according to the present disclosure can be used to manufacture a fuel cell separator having improved drainage properties while ensuring electrical conductivity through a simple process.

[0036] [Manufacturing method of fuel cell separator] The manufacturing method of the fuel cell separator of the present disclosure will be described using one embodiment. The one embodiment is a manufacturing method of the fuel cell separator 100 using the above-mentioned fuel cell separator material 50. A flow chart of the manufacturing method of the one embodiment is shown in Fig. 2. Also, a schematic diagram for explaining the manufacturing method of the one embodiment is shown in Fig. 3.

[0037] 2 and 3, the manufacturing method of one embodiment includes a separator material preparation step S1 for preparing the above-mentioned separator material 50, a heat forming step S2 for imparting an uneven shape 60 that will become a flow path to the surface of the separator material 50, and a removal step S3 for immersing the separator material 50 in a polar solvent to remove the soluble resin layer 40 after the heat forming step S2. In this way, a fuel cell separator 100 can be manufactured.

[0038] <Separator material preparation process S1> In the separator material preparation step S1, a separator material 50 is prepared. The configuration and preparation method of the separator material 50 have been described above, and therefore will not be described here.

[0039] <Heat forming process S2> In the hot molding step S2, an uneven shape 60 that will become flow paths is imparted to the surface of the separator material 50. Typically, the uneven shape 60 is imparted by pressing a heated mold against the separator material 50.

[0040] The heating temperature of the mold is not particularly limited, and may be set to about the glass transition temperature of the binder resin 20 + 50°C. For example, it is in the range of 180°C to 200°C. The pressure with which the mold is pressed is not particularly limited, and may be any pressure that can properly impart the uneven shape 60. For example, it is in the range of 20 MPa to 50 MPa. The time for which the mold is pressed is not particularly limited, and may be any time that can properly impart the uneven shape 60. For example, it is 5 to 120 seconds. If the heat molding time is too long, there is a risk that the soluble resin layer 40 cannot be removed.

[0041] In one embodiment, in the heat molding step S2, a release agent does not need to be applied to the separator material 50. This is because the soluble resin layers 40 are disposed on both sides of the separator material 50.

[0042] <Removal process S3> The removal step S3 is carried out after the heat molding step S2, and involves immersing the separator material 50 in a polar solvent to remove (dissolve) the soluble resin layer 40. This results in the soluble resin layer 40 being completely removed from the separator material 50, and the separator 100 is obtained.

[0043] The type of polar solvent used in the removal step S3 is a soluble resin. layer 40 There is no particular limitation as long as the solvent can be removed. Examples include water, lower alcohols having C1 to C3 (e.g., ethanol), glycols, DMSO, phenol, and the like. In consideration of the ease of solvent removal, highly volatile water or ethanol may be used. Water may be selected from the viewpoints of ease of handling and safety.

[0044] In the removal step S3, the polar solvent may be heated. 40 The soluble resin layer 40 can be easily removed and dissolved. The heating temperature of the polar solvent may be, for example, 50° C. or higher, or 85° C. or higher. Although there is no particular upper limit, the heating temperature of the polar solvent may be 95° C. or lower. Furthermore, in the removal step S3, ultrasonic waves may be applied to the separator material 50. This allows the soluble resin layer 40 to be easily removed and dissolved. In the removal step S3, the time for which the separator material 50 is immersed in the polar solvent is not particularly limited, but may be, for example, 5 minutes to 30 minutes.

[0045] After the removal step S3, the obtained separator 100 may be dried. The drying method is not particularly limited, and may be natural drying or heat drying.

[0046] <Reasons why surface treatment is not required> Fig. 4 shows a schematic diagram illustrating a conventional method for manufacturing a fuel cell separator using a blast treatment as a surface treatment. As shown in Fig. 4, in the conventional manufacturing method, first, a sheet-shaped composite material 130 is prepared (step S11), the composite material 130 is heated and molded, and an uneven shape 160 is imparted to its surface (step S12). Then, a blast treatment is performed on the composite material 130 to which the uneven shape 160 has been imparted (step S13). In this manner, a separator is manufactured.

[0047] Thus, the sheet-like composite material 130 used in the conventional manufacturing method does not have a soluble resin layer on its surface. Therefore, when the composite material 130 is heated and molded, the conductive particles 110 move to the surface side of the composite material 130, but the binder resin 120 remains on the surface, and the conductive particles 110 cannot be exposed on the surface. Therefore, in the conventional manufacturing method, in order to ensure conductivity, a blasting treatment is performed on the surface of the protrusions 161 to expose the conductive particles 110. However, in such a blasting treatment, the protrusions 161 are mainly scraped off, and the recesses 162 and vertical walls 163 (especially the vertical walls 163) is hardly scraped off, and its surface is covered with binder resin 120. This reduces the drainage of the flow path. When the drainage of the flow path is low, problems such as flooding occur. In Patent Document 1, in order to solve such drainage problems, a hydrophilic resin is applied to recess 162 and vertical wall 163.

[0048] In contrast, in a manufacturing method according to one embodiment, in step S1, a separator material 50 is prepared in which soluble resin layers 40 are arranged on both sides of a sheet-like composite material 30. Then, the separator material 50 is heated and molded to impart an uneven shape 60 to the separator material 50. At this time, the conductive particles 10 move so as to sink into the surface of the composite material 30 (the interface between the composite material 30 and the soluble resin layer 40). The separator material 50 is then immersed in a polar solvent to remove the soluble resin layer 40, thereby obtaining a separator 100 in which the conductive particles 10 are exposed on the surface.

[0049] In this manner, in the manufacturing method of one embodiment, the soluble resin layers are formed on both sides of the composite material 30. 40 Since the soluble resin layer is disposed on the composite material 30, the conductive particles 10 can be moved to the surface of the composite material 30 during heat molding. In other words, the conductive particles 10 can be selectively exposed on the surface of the composite material 30. 40 Therefore, the separator 100 produced by the manufacturing method of one embodiment has the conductive particles 10 on the surface (the protrusions). 61 , recess 62 , and Vertical Wall 63 Since the fluorine-containing polymer is smoothly exposed on all surfaces (including the surface of the substrate), no surface treatment such as blasting is required. Also, since no surface treatment is required, there is no need to wash off abrasives such as blasting materials.

[0050] <Soluble resin layer 40 Advantages of using During hot molding, a release agent is usually applied to make the material easier to remove from the mold. In conventional manufacturing methods, a soluble resin layer is not disposed on the surface of the composite material 130, so the release agent is applied directly to the composite material 130. In this case, the release agent permeates into the composite material 130. The permeated release agent may be released within the fuel cell and contaminate the power generation elements such as MEGA, thereby reducing the fuel cell performance.

[0051] In contrast, in one embodiment of the manufacturing method, the separator material 50 Soluble resin layer on both sides 40 By providing the mold release agent, the contact between the binder resin 20 and the mold is suppressed, and therefore the application of the mold release agent is not required. Therefore, the above-mentioned problems do not occur.

[0052] Also, as in Patent Document 2, there is a technique in which a separator material in which a release layer is arranged on both sides of a sheet-like composite material is heated and molded, and then the release layer is removed to manufacture a separator. Such a technique can certainly expose conductive particles on the surface. However, after the heat molding, the release layer may remain on the separator. If the release layer remains on the separator, there is a concern that the conductivity may decrease. In addition, in order to completely remove the release layer after the heat molding, the release layer needs to have a certain thickness or more, and there are restrictions on the elongation rate and heat resistance of the material so that it does not break. Therefore, it is necessary to use an expensive resin for the release layer. Furthermore, if the release layer is made thicker than a certain thickness, there is a risk that the transfer of the uneven shape cannot be performed properly.

[0053] In contrast, in one embodiment of the manufacturing method, the separator material is simply 50 The soluble resin layer is formed by immersing the layer in a polar solvent. 40 This is an advantage because it can completely remove the soluble resin layer. 40 The layer only needs to be soluble in a polar solvent, and does not need to be thicker than necessary like a release layer, so the uneven shape 60 It is also easy to transfer.

[0054] The manufacturing method of the fuel cell separator according to the present disclosure has been described above using one embodiment. According to the manufacturing method of the fuel cell separator according to the present disclosure, it is possible to manufacture a fuel cell separator with improved drainage while ensuring electrical conductivity. In addition, since no surface treatment such as blasting is required, the fuel cell separator can be manufactured through a simple process.

[0055] [Fuel cell separators] The fuel cell separator of the present disclosure will be described using a fuel cell separator 100 as one embodiment. The fuel cell separator 100 is manufactured by the manufacturing method described above. Fig. 5 shows a schematic cross-sectional view of the separator 100. Fig. 6 shows an enlarged schematic cross-sectional view of the separator 100.

[0056] The separator 100 is formed from a composite material 30 containing conductive particles 10 and a binder resin 20, and has an uneven surface 60 that serves as a flow path. The composite material 30 has been described above, so a description thereof will be omitted here.

[0057] <Uneven shape 60> As shown in Fig. 5, the separator 100 (composite material 30) has an uneven shape 60 on its surface that serves as a flow path. The uneven shape 60 has protrusions 61, recesses 62, and vertical walls 63 that connect the protrusions 61 and the recesses 62. The flow path is a flow path for circulating a fuel gas, an oxidant gas, or a coolant in a fuel cell. Typically, a flow path for a fuel gas or an oxidant gas is formed on one surface of the separator 100, and a flow path for a coolant is formed on the other surface.

[0058] (Protruding part 61) The protrusions 61 are portions that come into contact with a power generating element such as an MEA or MEGA in a fuel cell, and serve to ensure electrical conductivity between the separator 100 and the power generating element. The protrusions 61 have conductive particles 10 exposed on their surfaces, thereby ensuring electrical conductivity.

[0059] The surface roughness of the protrusions 61 is not particularly limited, but may be, for example, 0.1 μm or more, 0.5 μm or more, 2 μm or less, or 1.8 μm or less. When the surface roughness of the protrusions 61 is in the above range, the conductive particles 10 are sufficiently exposed on the surface, and the conductivity can be improved.

[0060] The water contact angle of the surface of the protrusions 61 is not particularly limited, but may be, for example, 80° or less. ° When the water contact angle is equal to or less than this value, it indicates that the conductive particles 10 are sufficiently exposed on the surface, and the conductivity can be improved. This effect is improved as the water contact angle is smaller.

[0061] In the present disclosure, the surface roughness can be measured using a microscope in accordance with ISO 25178. The water contact angle can be measured using a contact angle meter by the liquid drop method (JIS R 3257).

[0062] (Recess 62) The recess 62 is a portion that forms the bottom surface of the flow path. The conductive particles 10 are exposed on the surface of the recess 62. This ensures drainage.

[0063] The surface roughness of the recesses 62 is not particularly limited, but may be, for example, 0.1 μm or more, 0.5 μm or more, 2 μm or less, or 1.8 μm or less. When the surface roughness of the recesses 62 is in the above range, the conductive particles 10 are sufficiently exposed on the surface, and the drainage property can be improved.

[0064] The water contact angle of the surface of the recess 62 is not particularly limited, but may be, for example, 80° or less. Recess 62 The water contact angle is 80 ° When the water contact angle is equal to or less than this value, it indicates that the conductive particles 10 are sufficiently exposed on the surface, and the drainage property can be improved. This effect is improved as the water contact angle is smaller.

[0065] (Vertical wall 63) The vertical walls 63 are portions that form the side surfaces of the flow path. The conductive particles 10 are exposed on the surfaces of the vertical walls 63. This ensures drainage.

[0066] The separator 100 has one feature in the configuration of the vertical walls 63. That is, the surface roughness of the vertical walls 63 is 0.1 μm or more and 2 μm or less, and the water contact angle is 80° or less. This indicates that the conductive particles 10 are sufficiently exposed on the surface, and the drainage performance can be improved.

[0067] The surface roughness of the vertical wall 63 may be set to 0.5 μm or more and 1.8 μm or less. The smaller the water contact angle of the vertical wall 63, the more improved the above effect.

[0068] The fuel cell separator of the present disclosure has been described above using one embodiment. The fuel cell separator of the present disclosure can improve drainage while ensuring electrical conductivity. EXAMPLES

[0069] The present disclosure will now be further described with reference to examples.

[0070] [Making the separator] The separators of the example and comparative examples 1 to 4 were produced by the following method.

[0071] <Example 1> The base resin, curing agent, and reinforcing agent shown in Table 1 were dissolved in a solvent (methyl ethyl ketone), stirred, and then a curing accelerator dissolved in methanol was added to prepare a binder resin (epoxy resin). Then, conductive particles (a mixture of graphite powder and carbon fiber, graphite powder:carbon fiber = 14:1 (weight ratio)) were added and stirred. The obtained mixture was applied to a release film using a bar coater and dried to obtain a sheet-shaped composite material (thickness 600 μm). In the composite material, the ratio of conductive particles to binder resin was conductive particles:binder resin = 75:25 (weight%). In addition, polyvinyl alcohol dissolved in pure water was applied to a release film using a bar coater and dried to obtain a sheet-shaped soluble resin layer (thickness 5 μm). The obtained soluble resin layer was attached to both sides of the composite material to obtain a separator material.

[0072] Next, the separator material was press molded (heat molded) using a mold under conditions of 180°C, 1 minute, and 30 MPa to give it an uneven shape. The pressed separator material was then immersed in 80°C hot water for 10 minutes to completely remove the soluble resin layer. During this process, ultrasonic waves were applied to the hot water to agitate it. Finally, the obtained separator was heated to 100°C and dried for 1 hour to obtain the separator of Example 1.

[0073] <Comparative Example 1> The separator of Comparative Example 1 was obtained by applying a release agent to a sheet-shaped composite material (produced in Example 1) as shown in Table 2, and then hot-molding the composite material under the same conditions as in Example 1.

[0074] <Comparative Example 2> The separator of Comparative Example 2 was obtained by applying a release agent to a sheet-shaped composite material (produced in Example 1) as shown in Table 2, heat-molding the composite material under the same conditions as in Example 1, and then carrying out a blast treatment.

[0075] <Comparative Example 3> The separator of Comparative Example 3 was obtained by applying a release agent to a sheet-shaped composite material (produced in Example 1) as shown in Table 2, heat-molding the composite material under the same conditions as in Example 1, and then performing laser treatment.

[0076] <Comparative Example 4> The separator of Comparative Example 4 was obtained by preparing a separator material in which an insoluble resin layer (PET film, thickness 12.5 mm) was placed on both sides of a sheet-shaped composite material (prepared in Example 1) as shown in Table 2, and then hot-molding the material under the same conditions as in Example 1, and then peeling off the insoluble resin layer.

[0077] [Table 1]

[0078] [Table 2]

[0079] [evaluation] The performance of the separators of the example and comparative examples 1 to 4 was evaluated.

[0080] <Conductivity evaluation> As shown in Figure 7, two separators S were attached to each other, and a gas diffusion layer G and a gold-plated electrode E were placed on the outside of the separators. The pressure was then increased to an average surface pressure of 1.0 MPa, and then reduced to an average surface pressure of 0.8 MPa. The potential difference between the electrodes was measured and the resistance of the separator was calculated. Each test was performed three times. The results are shown in Table 3.

[0081] [Table 3]

[0082] According to Table 3, the resistance value of the Example was the lowest. This is believed to be because the ratio of conductive particles exposed on the surface of the convex portion was the highest compared to Comparative Examples 1 to 4. Since Comparative Example 4 had the highest resistance value, the evaluation described below was not performed.

[0083] <Drainage evaluation> Convex and concave parts of the separator, Vertical wallThe water contact angle of each of the samples was measured. The measurement was performed using a contact angle meter (Kyowa Interface Science, automatic extremely small contact angle meter MCA-J2) according to the liquid drop method (JIS R The results are shown in Figure 8.

[0084] From FIG. 8, the convex portion, concave portion, and Vertical wall In all regions, the water contact angle of the separator of the Example was smaller than that of Comparative Examples 1 to 3. This suggests that the Example has higher drainage than Comparative Examples 1 to 3. This result also suggests that the ratio of conductive particles on the surface of the separator of Example 1 is higher than that of Comparative Examples 1 to 3 in all regions.

[0085] <Surface roughness evaluation> Using a microscope (Keyence, VHX-7000), the surface roughness of the separator's protrusions was measured in a non-contact manner at three arbitrary points, and the average value was calculated in accordance with ISO 25178. The results are shown in Table 4.

[0086] [Table 4]

[0087] From Table 4, the surface roughness of Example 1 was the smallest. This indicates that the exposed conductive particles were smooth. It was found that there was no significant difference in the surface roughness of the convex portions, concave portions, or vertical walls of the separators of the examples. [Explanation of symbols]

[0088] 10, 110 Conductive particles 20, 120 Binder resin 30, 130 Composite materials 40 Soluble resin layer 50 Separator material 60, 160 uneven shape 61, 161 Convex 62, 162 recess 63, 163 Vertical wall 100 separator

Claims

1. A composite material including conductive particles and a binder resin; and a soluble resin layer disposed on both sides of the composite material. A fuel cell separator material, comprising: A fuel cell separator material, the surface of which does not have any irregularities that serve as flow paths.

2. the soluble resin layer contains a soluble resin that is soluble in a polar solvent, The soluble resin includes at least one selected from polyvinyl alcohol, celluloses, polyacrylic acid, and starch; The fuel cell separator material according to claim 1 .

3. The thickness of the soluble resin layer is 0.5 μm or more and 10 μm or less.

3. A fuel cell separator material according to claim 1 or 2.

4. A manufacturing process for manufacturing the fuel cell separator material according to claim 1 or 2; a heat forming step of forming a surface of the separator material into an uneven shape that will become a flow path; and a removing step of removing the soluble resin layer by immersing the separator material in a polar solvent after the hot molding step. A method for manufacturing a separator for a fuel cell.

Citation Information

Patent Citations

  • Fuel cell separator molding member and its manufacturing method, and manufacturing method for fuel cell separator using fuel cell separator molding member

    JP2006128027A

  • Polyelectrolyte fuel cell and its manufacturing method

    JP2006318717A

  • Fuel cell separator, method of manufacturing fuel cell separator and fuel cell

    JP2008135299A

  • Hydrophilic separator, and method of manufacturing the same

    JP2012160406A

  • Fuel cell separator, and method for manufacturing fuel cell separator

    JP2015038840A